2021
DOI: 10.2991/ijcis.d.210205.001
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Acute Ischemic Stroke Lesion Segmentation Using Semi-supervised Learning

Abstract: Ischemic stroke has been a common disease in the elderly population, which can cause long-term disability and even death. However, the time window for treatment of ischemic stroke in its acute stage is very short. To fast localize and quantitively evaluate the acute ischemic stroke (AIS) lesions, many deep-learning-based lesion segmentation methods have been proposed in the literature, where a deep convolutional neural network (CNN) was trained on hundreds of fully-labeled subjects with accurate annotations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Liu et al [64] used a U-shaped network (Res-CNN) to automatically segment acute ischemic stroke lesions from multimodality MRIs, and the average Dice coefficient was 0.742. Zhao et al [65] proposed a semisupervised learning method using the weakly labeled subjects to detect 6…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [64] used a U-shaped network (Res-CNN) to automatically segment acute ischemic stroke lesions from multimodality MRIs, and the average Dice coefficient was 0.742. Zhao et al [65] proposed a semisupervised learning method using the weakly labeled subjects to detect 6…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Liu et al [ 64 ] used a U-shaped network (Res-CNN) to automatically segment acute ischemic stroke lesions from multimodality MRIs, and the average Dice coefficient was 0.742. Zhao et al [ 65 ] proposed a semisupervised learning method using the weakly labeled subjects to detect the suspicious acute ischemic stroke lesions and achieved a mean Dice coefficient of 0.642. Compared to using MRI, a 2D patch-based deep learning approach was proposed to segment the acute stroke lesion core from CT perfusion images [ 66 ], and the average Dice coefficient was 0.49.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…However, the fully labeled annotation of lesions from a large number of images is tremendously labor and time intensive. Recently, some weakly supervised approaches were proposed to leverage the annotation workload (12)(13)(14), such as the wiseDNN (15) and the 3D weakly supervised network (16). The related studies have indicated that weakly supervised approaches can reduce the difficulty of label acquisition while still maintaining high detection efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have investigated medical image segmentation [3]- [5]. Recently, deep learning-based approaches have shown extraordinary potential in medical image segmentation tasks, especially for convolutional neural networks (CNNs) [6]- [11].…”
Section: Introductionmentioning
confidence: 99%